Ἕως ἂν κατέλθωσιν εἰς τὴν αὐτῶν: Did the Athenians Reduce their Reception of Refugees in the Fourth Century BC? - Laura Loddo (Pallas, 2020)
The Athenian public discourse between V and IV centuries BC displayed an image of Athens as an open city towards the outsiders and as a protector of the weak and the oppressed (section 1). Although scholars frequently stressed the Athenian reluctance on naturalization of foreigners, it is a fact that the Athenians showed themselves as well disposed towards the political exiles who took refuge in Attica according them welcome and protection (section 2 and 3). From the middle of the IV century, however, a limitation to the reception of refugees and to the rights connected to the status of refugee appears in the epigraphic sources, since such reception is assured only until they returned home. After having illustrated the content and nature of the inscriptions bearing this formula (section 4), I offer an explanation of the meaning of such limitation taking in consideration both the socio-political background and the Greek perception of the political exile (section 5).